Hasil validasi bahan ajar fisika melalui pendekatan konstruktivisme bernuansa hikmah pada materi hukum newton gravitasi dan momentum impuls untuk kelas X SMA/MA - lara agustia; Letmi Dwiridal (Universitas Negeri Padang, 2019)
This research is motivated by physics learning which is still centered on the teacher and the limited of teaching materials that can be used by students so that students have difficulty in understanding the subject matter. Physics learning requires students to search, experience, explore, and discover for themselves. The purpose of this research is to produce physics teaching materials through a valid nuanced boon constructivism approach and to find out the validity of physics teaching materials through a nuanced boon constructivism approach. Research conducted includes the steps of research and development according to Sugiyono. The stages carried out in this study, that is:1) potential and problems, 2) data collection, 3) product design, 4) design validatian, 5) design revision. The feasibility test was conducted in the form of a validity test by three physics lecturers at the Faculty of Mathematics and natural science of Padang State University and Three teachers from different schools, which is State High School four of Pariaman, State High School one of Nan Sabaris, and State High School two of Batang Anai. Data collection was performed using a validity instrument which was then analyzed using a Likert scale. Based on research that has been done, produced products in the form of teaching material through a nuanced boon constructivism approach on Newton’s law of gravity and impulse momentum. The product that has been made is rated highly valid from several components of content worthiness, linguistic component, presentation component and grapich component with a percentage of the average value obtained which is 83,5. This teaching material can later be carried out practicality test and effectiveness tests that will be developed by future researchers so that they can be used in learning activities.